2022
DOI: 10.3389/fpsyt.2021.809040
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Psychological Distress and Its Relationship to Sleep Quality in Saudi Arabia's General Population During the COVID-19 Pandemic

Abstract: BackgroundWe aimed to examine the effect of the COVID-19 pandemic and associated mitigation measures on sleep quality and psychological distress in Saudi Arabia.MethodsSubjective sleep quality over the preceding 30 days was measured using the Pittsburgh Sleep Quality Index (PSQI). In addition, Kessler Psychological Distress Scale (K10) was used to assess the psychological distress.ResultsThe study included 836 participants. The median age was 28 years, 624 (74.64%) were females, and 158 (18.90%) were healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In this study, about 3% of patients had a K10 score above 30, indicating they were under severe psychological distress [ 34 , 35 ]. Kessler et al [ 36 ] suggested that about 6% of Americans may suffer from severe mental disorder, and this result was also supported by other studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, about 3% of patients had a K10 score above 30, indicating they were under severe psychological distress [ 34 , 35 ]. Kessler et al [ 36 ] suggested that about 6% of Americans may suffer from severe mental disorder, and this result was also supported by other studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the region reported lower sleep efficiency, another measure of sleep quality, of 25.5% in females and 13.3% in males [50]. Sleep quality has been reported to have been affected by the pandemic, probably because of the pandemic-related challenges impacting people's lifestyles and mental wellbeing [51] and because of their fears and the spread of misinformation about the pandemic [52]. It is also important to note that poor sleep quality has been attributed to stressful factors of the COVID-19 pandemic, including lockdowns and news about the pandemic [53] and that this stress could be higher in certain groups of populations than others.…”
Section: Discussionmentioning
confidence: 99%
“…The study further reported that distress was associated with recent changes in sleep habits, fear-related to coronavirus news, and lack of treatment for coronavirus. 34 A large study in Bahrain 35 also showed that the pandemic had a significant psychological impact on Bahrain’s population, with almost one-third of the population experiencing some level of discomfort and anxiety symptoms.…”
Section: Reported Findings In the Literaturementioning
confidence: 99%